RBP1 Recruits Both Histone Deacetylase-Dependent and -Independent Repression Activities to Retinoblastoma Family Proteins - Lai, Albert (American Society for Microbiology, 1999)
Retinoblastoma (RB) tumor suppressor family proteins block cell proliferation in part by repressing certain E2F-specific promoters. Both histone deacetylase (HDAC)-dependent and -independent repression activities are associated with the RB “pocket.” The mechanism by which these two repression functions occupy the pocket is unknown. A known RB-binding protein, RBP1, was previously found by our group to be an active corepressor which, if overexpressed, represses E2F-mediated transcription via its association with the pocket. We show here that RBP1 contains two repression domains, one of which binds all three known HDACs and represses them in an HDAC-dependent manner while the other domain functions independently of the HDACs. Thus, RB family members repress transcription by recruiting RBP1 to the pocket. RBP1, in turn, serves as a bridging molecule to recruit HDACs and, in addition, provides a second HDAC-independent repression function.